Penyusunan Akta Perjanjian Elektronik dalam Hukum Keperdataan: Peran Notaris dan Tanggung Jawab Hukum - Juliani, Amelia Dwi (Faculty of Law Universitas Islam Indonesia, 2024)
The drafting of electronic agreements in civil law in Indonesia is increasingly relevant with the rapid development of information technology and digitalization of legal services. This has been accommodated through Law Number 11 of 2008 concerning Electronic Information and Transactions, which has been amended through Law Number 19 of 2016 and most recently by Law Number 1 of 2024. Despite having a legal basis, the implementation of electronic deeds still faces various significant challenges, especially in terms of validity, authentication, and legal protection for the parties involved. The problem formulation in this study is to examine the responsibilities and roles of notaries in the drafting of electronic agreements. This article aims to examine in depth the role of notaries in the drafting of electronic agreements, as well as the legal responsibilities inherent in notaries as public officials who guarantee legal certainty and protection. This research uses a normative juridical approach by analyzing relevant regulations, including Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary Public. The role of a notary in electronic agreements includes identity verification, the authenticity of electronic signatures, transaction process supervision, and maintaining the integrity of electronic data. A notary's legal responsibilities include data confidentiality, electronic system security, and the legal validity of the agreement. Therefore, more detailed regulations, education for notaries, and strengthened oversight are needed to ensure the continuity of the electronic deed system in civil law in Indonesia